Microleakage and bacterial adhesion with three restorative materials used to seal screw-access channels of implant abutments: An in vitro study - Firas Khalid AlQarawi (Saudi Journal of Medicine and Medical Sciences, 2021)
Background: Proper sealing of screw-access channels against microbial microleakage is advisable for the long-term success of screw-retained implant prosthesis. Objective: This study aimed to compare the bacterial adhesion and microleakage with three restorative materials, namely, composite resin, acrylic resin and bis-acryl, that are used to cover the access channels of screw-retained implant prostheses, using polytetrafluoroethylene tape as a spacer material. Materials and Methods: In this in vitro study, 18 titanium straight abutments (Hex-lock® Zimmer) were torqued into implant analogs, which were then subdivided into three groups. The samples of each group were filled with polytetrafluoroethylene tape and sealed with the three restorative materials (Group A: composite resin; Group B: acrylic resin; Group C: bis-acryl). Measurements of surface bacterial adhesion and internal microleakage were then recorded. The results were statistically analyzed using Kruskal–Wallis and Chi-square tests. Results: No significant difference was found between the investigated materials in terms of their sealing effectiveness against microbial microleakage (P = 0.06). Regarding bacterial adhesion, composite resin showed the highest number of surface adhesion, but there was no significant difference between the three materials (P = 0.081). Conclusion: The results of this study suggest that composite resin, acrylic resin and bis-acryl materials could be used alternatively in sealing the implant access channel owing to no significant differences in terms of microleakage and bacterial adhesion.